Deep distortion. Issue 1 (2nd January 2022) - Brainerd, C. J.
ABSTRACT: Conventional false memories recount events that either did not happen (item errors) or that happened in a different context (source errors). Fuzzy-trace theory predicts deeper anomalies that lie behind conventional false memories. These deep distortions are structural irregularities in the ways that specific recountings are related to each other or to some objective standard (e.g., the 0 and 1 limits of probability). I discuss five deep distortions for which substantial data have accumulated: overdistribution, non-additivity, conjunction illusions, non-compensation, and super-overdistribution. Together, these phenomena violate the disjunction and additivity axioms of probability, as well as the law of the excluded middle. The theoretical problem they pose is to explain how valid representations of our experience produce memory regularities that violate our experience in the most fundamental ways.